The Return of the King : Lord of the Rings #3 - Tolkien, J. R. R., 1892-1973, (John Ronald Reuel) (New York : Recorded Books, 1987)
The trilogy concludes as Frodo and Sam make a terrible journey to the heart of the land of the Shadow in a final reckoning with the power of Sauron.
Unabridged.
Subtitle on container: Part III of The lord of the rings.
Performed by Rob Inglis.
Also issued on cassette.
Compact disc.
Keywords: Tolkien, J. R. R. -- 1892-1973.; Middle Earth (Imaginary place) -- Drama; Audiobooks